A TES finfine detector for bolometric interferometry - Dunlop, L; Yassin, G; Goldie, D; Withington, S; Jones, M (2004)
In this paper we present a novel design of an antenna coupled TES direct detector for high performance applications. In particular, the design of the detector has been optimised to be suitable for the measurement of the weak B-mode signal in the CMB polarization. An important feature of this design is that it employs corrugated horn antennas for coupling the astronomical signal to the detector. This allows us to feed the telescope with a well collimated beam with low sidelobes and cross polarization. The paper contains simulations demonstrating the suitability of individual electromagnetic components to be used in the instrument.